Cardio-metabolic risk in individuals prescribed long-acting injectable antipsychotic medication. (November 2019) - Morell, Rachel; Curtis, Jackie; Watkins, Andrew; Poole, Josephine; Fibbins, Hamish; Rossimel, Elisa; Gerrard, Mark; White, Annette; Teasdale, Scott; Ward, Philip B.; Lappin, Julia
Highlights: High prevalence of metabolic syndrome and associated risk factors in people on LAIs. Individuals younger than 35 years 2.5 times more likely to have metabolic syndrome. Cardio-metabolic risk factors largely under- or un- treated. Abstract: People living with severe mental illness (SMI) experience significant physical health co-morbidity. Few studies have focused on physical health outcomes for those prescribed long-acting injectable (LAI) antipsychotics. This observational cross-sectional study aimed to assess the prevalence of metabolic syndrome (MetS) and other cardio-metabolic risk factors in a large cohort prescribed LAI and managed by community mental health services. For participants with elevated cardio-metabolic risk factors, the proportion receiving appropriate management was assessed. Of the 301 eligible participants, many met the full criteria for MetS (44%) and its components. Cardio-metabolic risk factors were largely under- or un-treated. Smoking rates were very high (62%) along with reported high rates of physical inactivity and poor dietary intake. The vast majority (89%) reported seeing their general practitioner in the preceding twelve months. Individuals prescribed LAI have a very high prevalence of MetS and potentially modifiable risk factors for cardiovascular disease. Routine monitoring accompanied by evidence-based treatment of cardiometabolic abnormalities which contribute to significant morbidity, disability and premature death should be prioritised. Better collaboration between mental health services and primary care providers should be pursued to optimise the delivery of effective physical health care to individuals living with SMI.